2020
DOI: 10.7554/elife.57068
|View full text |Cite
|
Sign up to set email alerts
|

MondoA regulates gene expression in cholesterol biosynthesis-associated pathways required for zebrafish epiboly

Abstract: The glucose-sensing Mondo pathway regulates expression of metabolic genes in mammals. Here, we characterized its function in the zebrafish and revealed an unexpected role of this pathway in vertebrate embryonic development. We showed that knockdown of mondoa impaired the early morphogenetic movement of epiboly in zebrafish embryos and caused microtubule defects. Expression of genes in the terpenoid backbone and sterol biosynthesis pathways upstream of pregnenolone synthesis was coordinately downregulated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…GFP-and RFP-fusions have been used to image plasma membranes and cell nuclei in Arabidopsis plants (figure 9(C)) [212] . Developmental studies on various model organisms have also been reported, including studies on the transparent zebrafish (Danio rerio) embryo, with GFP fusions for labeling cell nuclei (figure 9(D)) [213][214][215], the heart [216] or cells of the developing eye [217].…”
Section: Light Sheet Microscopymentioning
confidence: 99%
“…GFP-and RFP-fusions have been used to image plasma membranes and cell nuclei in Arabidopsis plants (figure 9(C)) [212] . Developmental studies on various model organisms have also been reported, including studies on the transparent zebrafish (Danio rerio) embryo, with GFP fusions for labeling cell nuclei (figure 9(D)) [213][214][215], the heart [216] or cells of the developing eye [217].…”
Section: Light Sheet Microscopymentioning
confidence: 99%
“…So, it was recently reported that treatment of HeLa cells with cycloheximide and other translation elongation inhibitors are able to activate the MondoA pathway [67]. As a member of the MLX family of glucose-sensing transcription factors, MondoA is not only a key regulator of the energy metabolism [30] but also plays an important role in the regulation of cholesterol/steroid metabolism [41,65].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, five genes that exhibited less dramatic downregulation were also selected for our downstream analyses because these genes are less thoroughly studied but have previously been associated with either autophagy or senescence (Levine and Kroemer, 2019;Wiley et al, 2016;Gorgoulis et al, 2019;Ravussin et al, 2021;Lee et al, 2019;Zidi et al, 2019). Although Txnip, which is induced by MondoA at high glucose concentrations (Stoltzman et al, 2008), was also significantly downregulated in both MondoA and Mlx knockdown cells exposed to DXR, we excluded Txnip from analyses hereafter because it has already been investigated in detail (Stoltzman et al, 2008;Ahn et al, 2016Ahn et al, , 2019Weger et al, 2020;Zhang et al, 2018Zhang et al, , 2019.…”
Section: Loss Of Mondoa Disrupts the Regulation Of Prdx3 And Rubiconmentioning
confidence: 99%
“…MondoA, a basic-helix-loop-helix-leucine zipper heterodimerization partner of Max-like protein X (Mlx) (Billin et al, 2000), senses cellular energy status at the mitochondrial outer membrane (Wilde et al, 2019) and activates transcription for meta-bolic genes including glycolytic enzymes (Sans et al, 2006;Stoltzman et al, 2008). Regulation of thioredoxin-interacting protein (Txnip) by MondoA participates in cholesterol/lipid metabolism, muscle lipid accumulation and insulin resistance, and tumorigenesis (Stoltzman et al, 2008;Ahn et al, 2016Ahn et al, , 2019Weger et al, 2020;Zhang et al, 2018). Interestingly, MondoA complexes promote longevity in response to a variety of signals, such as germline removal and calorie restriction in C. elegans (Nakamura et al, 2016;Johnson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%